2009
DOI: 10.1016/j.humimm.2009.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Increased number of CD16+CD56dim NK cells in peripheral blood mononuclear cells after allogeneic cord blood transplantation

Abstract: In the present study, we investigated subpopulations of NK cells and the expression of stimulatory and inhibitory NK receptors after adult blood and bone marrow transplantation (BBMT) and cord blood transplantation (CBT).There were significant increases in CD16 + CD56 dim cell proportion and absolute number in peripheral blood mononuclear cells (PBMC) during a period of 4 months to 9 months after CBT compared with these in normal PBMC, cord blood (CB) and in PBMC after BBMT.Also, increased number of CD16 + CD5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…However it is also possible that more prompt recovery of NK cells and B-cells in UCB recipients may compensate for early T-cell deficits, although rapid recovery of both of these cell types may partly be due to a compensatory response to the profound T-lymphopenia [37, 38]. Tanaka et al observed a more rapid expansion of NK cells following umbilical cord blood compared to peripheral blood stem cell transplantation [39]. The investigators found that a umbilical cord blood derived mature (CD16+, CD56 dim ) and immature (CD16−, CD56+) populations of NK cells exert potent cytotoxic activity against tumor cell lines and exhibit decreased expression of inhibitory NKG2A and increased expression of stimulatory NKG2C as compared to NK cells that emerge following matched related donor transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…However it is also possible that more prompt recovery of NK cells and B-cells in UCB recipients may compensate for early T-cell deficits, although rapid recovery of both of these cell types may partly be due to a compensatory response to the profound T-lymphopenia [37, 38]. Tanaka et al observed a more rapid expansion of NK cells following umbilical cord blood compared to peripheral blood stem cell transplantation [39]. The investigators found that a umbilical cord blood derived mature (CD16+, CD56 dim ) and immature (CD16−, CD56+) populations of NK cells exert potent cytotoxic activity against tumor cell lines and exhibit decreased expression of inhibitory NKG2A and increased expression of stimulatory NKG2C as compared to NK cells that emerge following matched related donor transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…18, 19 NK cell engraftment is earlier and more robust and T-cell engraftment is delayed after CBT. 20, 21 Therefore, CBT may represent a setting in which KIR ligand incompatibility is associated with protection from leukemia relapse. Willemze et al 22 reported transplantation outcomes after single-unit CBT for AML patients ( n =94) and ALL patients ( n =124).…”
Section: Discussionmentioning
confidence: 99%
“…7,10 Conversely, innate immunity recovery has been shown to be similar between CB and BM recipients, with normal cell counts of functional NK cells in the blood as soon as 1-month post-CBT. 2,11,12 Finally, B-cell number recovery appears to be faster after CBT. 6,9,13 Besides these differences in the reconstitution of the major lymphocyte populations, additional changes in the reconstitution of other immune cell subsets might occur and explain some of the clinical differences observed in patients who receive BMT or CBT.…”
Section: Introductionmentioning
confidence: 95%